Muslim Tourists' Perspectives on Halal and Muslim-Friendly Tourism in South Korea - Mustaqim, Muhamad; Hana, Kharis Fadlullah; Alimin, Masnaini (Indonesian Journal of Halal Research, 2025)
Identifying the needs of Muslim travelers is crucial for the tourism industry’s development, particularly as the demand for Muslim-friendly tourism increases alongside the global Muslim population. This study aims to understand the perspectives and factors influencing the needs of Muslim tourists with halal and Muslim-friendly tourism in South Korea. This study employs a qualitative phenomenological approach, collecting primary data from 18 semi-structured interviews conducted in Seoul, supplemented by secondary and observational data. The data were analyzed using qualitative data analysis software (QDA Miner Lite), and validity testing was conducted using internal and external validity tests. This research outlines the key requirements that South Korea, as a Muslim-minority country, must fulfill to establish a halal-friendly image, such as providing halal food, worship facilities, transportation, accommodation, safety, and destinations. Supported by various studies on the needs of Muslim tourists and the challenges in implementing these facilities, the findings emphasize the crucial roles of standardization, infrastructure, and cultural sensitivity in attracting and satisfying Muslim travelers. South Korea has made progress in developing travel facilities, but additional improvements in halal services and regulations are needed to better meet the needs of Muslim travelers.